2014
DOI: 10.3109/01480545.2014.963599
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavones have antimutagenic activity on DNA damage induced by the antileishmanial Glucantime (meglumine antimoniate)

Abstract: Isoflavones are phytoestrogens reported to be potent antioxidant agents. In contrast, the antileishmanial meglumine antimoniate has mutagenic activities. This study evaluated the ability of soy isoflavones to reduce DNA damage induced by meglumine antimoniate. Antimutagenic effects (by micronucleus test) were tested using Swiss mice divided into seven groups treated with meglumine antimoniate (425 mg/kg bw pentavalent antimony); cyclophosphamide (50 mg/kg bw); water (negative control); single isoflavones dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…According to Singh et al (50), high ROS production, such as that observed in the oxidative burst, may lead to saturation of this antioxidant pathway due to the large consumption of GSH by GPx. These observations are in line with our results, especially because it has been shown that Sb III is able to impair the redox balance by promoting intracellular GSH depletion and glutathione reductase inhibition, thereby preventing GSH regeneration (14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…According to Singh et al (50), high ROS production, such as that observed in the oxidative burst, may lead to saturation of this antioxidant pathway due to the large consumption of GSH by GPx. These observations are in line with our results, especially because it has been shown that Sb III is able to impair the redox balance by promoting intracellular GSH depletion and glutathione reductase inhibition, thereby preventing GSH regeneration (14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with the fact that Sb III is a borderline metal ion with a high affinity for nitrogen-and sulfhydryl-containing ligands (25). Our results also support the findings of Cantanhêde et al (18), who showed that soybean isoflavone, a potent antioxidant, was able to reduce the genetic damage caused by meglumine antimoniate.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations